Centrally provided student academic and transition support services and programs. - Supple, Briony; Wojtaszek, Sylwia; Fotinatos, Nina (Australia. Dept of Education and Training (DET), 2018)
This case report presents key findings from the Federation University (FedUni) Case Study as part of the OLT Strategic Priority project, Shaping the 21st century student experience at regional universities (SP14-4602). Six staff and seven students participated in an exploratory qualitative research project which investigated the relationship between central student academic and transition support services and programs (SS&Ps) and student motivation, emotion, well-being and satisfaction. This scope of project includes the following SS&Ps: Mentors; ASK Service; FedReady; yourtutor; Study Skills Website; Peer Assisted Study Sessions (PASS). A summary of the case study is also available, published as: Student support promotes 21st Century student engagement in a regional context.